A Panel Estimation of the Relationship Between Trade Liberalization, Economic Growth and CO2 Emissions in BRICS Countries - Mehrara Mohsen; Abbas ali Rezaei (Hyperion Economic Journal, 2013)
In the last few years, several studies have found an inverted-U relationship between per capita income and environmental degradation. This relationship, known as the environmental Kuznets curve (EKC), suggests that environmental degradation increases in the early stages of growth, but it eventually decreases as income exceeds a threshold level. However, this paper investigation relationship between per capita CO2 emission, growth economics and trade liberalization based on econometric techniques of unit root test, co-integration and a panel data set during the period 1960-1996 for BRICS countries. Data properties were analyzed to determine their stationarity using the LLC , IPS , ADF and PP unit root tests which indicated that the series are I(1). We find a cointegration relationship between per capita CO2 emission, growth economics and trade liberalization by applying Kao panel cointegration test. The evidence indi cates that in the long-run trade liberalization has a positive significant impact on CO2 emissions and impact of trade liberalization on emissions growth depends on the level of income Our findings suggest that there is a quadratic relationship between relationship between real GDP and CO2 emissions for the region as a whole. The estimated long-run coefficients of real GDP and its square satisfy the EKC hypothesis in all of studied countries. Our estimation shows that the inflection point or optimal point real GDP per capita is about 5269.4 dollars. The results show that on average, sample countries are on the positive side of the inverted U curve. The turning points are very low in some cases and very high in other cases, hence providing poor evidence in support of the EKC hypothesis. Thus, our findings suggest that all BRICS countries need to sacrifice economic growth to decrease their emission levels